Age-related patterns in human myeloid dendritic cell populations in people exposed to Schistosoma haematobium infection. - Norman Nausch; Delphine Louis; Olivier Lantz; Isabelle Peguillet; François Trottein; Isobel Y D Chen; Laura J Appleby; Claire D Bourke; Nicholas Midzi; Takafira Mduluza; Francisca Mutapi (PLoS Neglected Tropical Diseases)
Background Urogenital schistosomiasis is caused by the helminth parasite Schistosoma haematobium. In high transmission areas, children acquire schistosome infection early in life with infection levels peaking in early childhood and subsequently declining in late childhood. This age-related infection profile is thought to result from the gradual development of protective acquired immunity. Age-related differences in schistosome-specific humoral and cellular responses have been reported from several field studies. However there has not yet been a systematic study of the age-related changes in human dendritic cells, the drivers of T cell polarisation. Methods Peripheral blood mononuclear cells were obtained from a cohort of 61 Zimbabwean aged 5-45 years with a S. haematobium prevalence of 47.5%. Two subsets of dendritic cells, myeloid and plasmacytoid dendritic cells (mDCs and pDCs), were analyzed by flow cytometry. Findings In this population, schistosome infection levels peaked in the youngest age group (5-9 years), and declined in late childhood and adulthood (10+ years). The proportions of both mDCs and pDCs varied with age. However, for mDCs the age profile depended on host infection status. In the youngest age group infected people had enhanced proportions of mDCs as well as lower levels of HLA-DR on mDCs than un-infected people. In the older age groups (10-13 and 14-45 years) infected people had lower proportions of mDCs compared to un-infected individuals, but no infection status-related differences were observed in their levels of HLA-DR. Moreover mDC proportions correlated with levels of schistosome-specific IgG, which can be associated with protective immunity. In contrast proportions of pDCs varied with host age, but not with infection status. Conclusions Our results show that dendritic cell proportions and activation in a human population living in schistosome-endemic areas vary with host age reflecting differences in cumulative history of exposure to schistosome infection.